Changes of crystallite sizes in the oxide layer forming during long-term operation of 10CrMo9-10 steel - Gwoździk, Monika (Technical Sciences, 2017)
The paper contains results of the studies on X-ray diffraction analysis XRD (studying the phase composition, crystallite sizes) of oxide layers on 10CrMo9-10 steel, operated for a long time at an elevated temperature (T = 525°C, t = 200,000 h). The oxide layer was studied on a surface and a cross-section at the outer on the inlet both on the fire and counter-fire side of the tube wall surface. X-ray studies were carried out on the outer surface of a tube, and then the layer surface was polished down and the diffraction measurements were performed again to determine crystallite size in oxide layers. Based on the width and the position of the main coat and substrate reflections, the size of the crystallites was determined using the Scherrer formula.